Factors Influencing Turnover Intention Among Generation Z Employees in Financial Companies - Shofa, Muhammad (International Journal of Education, Vocational and Social Science, 2025)
Generation Z presents unique challenges for organizations, especially in the financial sector, with high expectations for work-life balance, flexibility, and individual recognition. This study aims to identify factors influencing turnover intention among Generation Z employees in financial companies. The research methodology involves a literature review using a bibliometric approach with VOSviewer. A total of 23 articles were selected from 65 articles based on inclusion criteria. The analysis results indicate that the main factors driving turnover intention are job insecurity, role overload, work-life balance, work environment, and leadership style. Generation Z is more sensitive to job insecurity and excessive workloads, affecting their loyalty to companies. Strategies such as flexible working hours, hybrid work policies, and structured career development can help reduce turnover intention. This study provides managerial insights suggesting that companies need to adopt more adaptive approaches, including enhancing communication, creating inclusive work environments, and building strong employer branding. The implications of this research are relevant in helping financial companies improve employee retention and create long-term operational stability.